On the Categories of Possibility, Limiting Conditions and the Qualitative Development Stages of Matter in the Thought of Friedrich Engels - Klaus Fuchs-Kittowski (tripleC: Communication, Capitalism & Critique)
The contradictory character of matter is the starting point of Friedrich Engels’s dialectical principles. Matter can move itself, thus producing ever new possibilities of development and gradually leading to the formation of qualitatively higher forms of movement of matter. In this dialectical conception of development, the explanation of qualitative change is fundamental. Starting from the understanding that the inner contradiction is the source of development and its potential, the transition to a new quality is verifiable.  Probabilistic laws are the expression of the unity of necessity and chance in the real possibility. Limiting conditions, like specific structures, informational coupling and whole-part relationships and selection processes, restrict the field of possibilities opened by physical laws. This restriction of possibilities on the lower level opens up new possibilities of development on the higher level, where the transition to a new quality is realised. Materialist and dialectical thinking is the important basis of a theory of biology that is neither physicalist nor vitalist, of a theory of computer science that is neither physicalist nor dualist. Mechanistic thinking – reductionism, the denial of the specific qualities of the different forms of movement of matter – leads to philosophies that reduce the human being to an animal or computer and is both dangerous and inhuman. Computer science needs to engage with the history and application of materialistic and dialectical thinking. It needs to grasp the dialectical unity of similarity and difference between automaton and human in the concrete process of digitalisation and automation. It must overcome the widespread, increasing interest in reducing the human being to an automaton, in order to maintain the unique quality of the human being. It must protect and enhance the special qualities and abilities of human beings. The danger of anti-dialectical thinking, of modern forms of reductionism and the possibility, indeed necessity, of creating a better society, free from profit, greed and war is discussed in this paper in the context of Engels’s 200th birthday.